(untitled) (Malaysian Journal of Civil Engineering, 2018)
Bond in concrete plays a crucial role in the performance of reinforced concrete structures which are influenced by several factors such as concrete compressive strength, diameter, type and embedment length of bar, confinement of concrete etc. This paper discusses experimental investigation on bond strength behaviour of geo polymer concrete (GPC). The influence of compressive strength and embedment length of reinforcing bar on the bond strength of GPC has been reported. A total of 27 GPC prisms were tested by conducting pull out tests. Three grades of GPC (G20, G35 and G50) and three embedment lengths (75mm, 100mm and 125mm) were used in this study. The results indicated that the bond strength has increased with increase in compressive strength. The bond strength of reinforcing bars in geopolymer concrete decreases with increasing the embedment length.